Depth Psychology of Art. - McNiff, Shaun (Charles C Thomas Publisher, LTD, 1989)
By Shaun McNiff, Endicott College, Beverly, Massachusetts. CONTENTS: Introduction; Nomenclature; Interpretation; Re-Imagining the Artist as a Therapist; Self Inquiry. Bibliography.